Change in grip strength, hang time, and knot tying speed after 24 hours of endurance rock climbing - Yu, E.; Lowe, J.; Millon, J.; Tran, K.; Coffey, C. (Frontiers in Sports and Active Living, 2023)
Background: Non-professional climbers are increasingly attempting long routes in a single day. Many suffer injury or rely on search and rescue teams when they become too fatigued to finish. Predicting fatigue is difficult, and existing studies have only studied climbers over durations less than an hour, while many outdoor multipitch climbs require more than an hour of climbing.